American grape wines: The Vitis labrusca X-factor - de Castilhos, Maurício Bonatto Machado (2021)
Wine is one of the most famous beverages in the world, and the principal wine producers worldwide are European countries, which are known as their high quality wines produced from Vitis vinifera grapes. In contrast to this scenario, Brazil is one of the countries that present a production of Vitis vinifera wines; however, the production of wines produced from Vitis labrusca grapes stands out in comparison with the great wine producers. Vitis labrusca grapes are underestimated in comparison with the Vitis vinifera grapes since the wines produced from the American grapes are sweet and fruity, and these sensory features are not very appreciated by the wine experts and consumers. However, the American grapes and their hybrids have, in their composition, a great number of phenolic compounds accounting for high antioxidant capacity, color indexes, and stability. Therefore, the importance of these grapes and wines should be highlighted since these wines, depending on the grape cultivar, present features that make them unique.